Immobilizing NIR absorbing azulenocyanines onto single wall carbon nanotubes - From charge transfer to photovoltaics - Ince, Mine; Bartelmeß, Jürgen; Kießling, Daniel; Dirian, Konstantin; Victoria Martinez-Diaz, M.; Torres, Tomas; Guldi, Dirk Michael (Chemical Science, 2012)
In this fundamental study, the supramolecular interactions between SWNTs and either symmetrical Zn(ii) octa-tert-butylazulenocyanine 1 or a Zn(ii) azulenocyanine-phthalocyanine 2 bearing a pyrene unit have been evaluated. The synthetic protocol allowed for the preparation of unsymmetrical azulenocyanine-phthalocyanine molecules, which incorporate reactive hydroxyl functional groups useful for the preparation of more elaborate derivatives, that is, the pyrene containing derivative 2 by an esterification reaction. To shed light onto the mutual interactions between 1 or 2 and SWNT, stable suspensions of SWNT in a mixture of 25% THF and 75% DMF were titrated with variable amounts of 1 or 2. These assays indicate a successful immobilization of azulenocyanine derivatives 1 or 2 onto SWNTs to yield the supramolecular hybrids SWNT/1 and SWNT/2. In this light, the physico-chemical properties of 1 and 2 as well as those of SWNT/1 and SWNT/2 were investigated. From these we conclude strong interactions in the ground state, and a rapid charge separation in the excited state of SWNT/1 or SWNT/2. The accordingly formed radical ion pair states decay with lifetimes of 124 and 137 ps for SWNT/1 and SWNT/2, respectively. Finally, SWNT/1 and SWNT/2 were integrated into photoelectrochemical cells, revealing a response throughout the visible and near-infrared with a moderate IPCE maxima of 2.5%. © 2012 The Royal Society of Chemistry.

Panchromatic light harvesting in single wall carbon nanotube hybrids - Immobilization of porphyrin-phthalocyanine conjugates - Bartelmeß, Jürgen; Soares, Ana R. M.; Victoria Martinez-Diaz, M.; Neves, Maria G. P. M. S.; Tome, Augusto C.; Cavaleiro, Jose A. S.; Torres, Tomas; Guldi, Dirk Michael (Chemical Communications, 2011)
We report on immobilizing H /Zn-porphyrin-Zn-phthalocyanine conjugates onto single wall carbon nanotubes and by using the excellent stability of the resulting suspensions we were able to demonstrate for the first time the sequence of energy transfer-electron transfer in SWNT donor-acceptor conjugates. © 2011 The Royal Society of Chemistry.

Phthalocyanine-pyrene conjugates: A powerful approach toward carbon nanotube solar cells - Bartelmeß, Jürgen; Ballesteros, Beatriz; De La Torre, Gema; Kießling, Daniel; Campidelli, Stephane; Prato, Maurizio; Torres, Tomas; Guldi, Dirk Michael (Journal of the American Chemical Society, 2010)
In the present work, a new family of pyrene (Py)-substituted phthalocyanines (Pcs), i.e., ZnPc-Py and H Pc-Py, were designed, synthesized, and probed in light of their spectroscopic properties as well as their interactions with single-wall carbon nanotubes (SWNTs). The pyrene units provide the means for non-covalent functionalization of SWNTs via π-π interactions. Such a versatile approach ensures that the electronic properties of SWNTs are not impacted by the chemical modification of the carbon skeleton. The characterization of ZnPc-Py/SWNT and H Pc-Py/SWNT has been performed in suspension and in thin films by means of different spectroscopic and photoelectrochemical techniques. Transient absorption experiments reveal photoinduced electron transfer between the photoactive components. ZnPc-Py/SWNT and H Pc-Py/SWNT have been integrated into photoactive electrodes, revealing stable and reproducible photocurrents with monochromatic internal photoconversion efficiency values for H Pc-Py/SWNT as large as 15 and 23% without and with an applied bias of +0.1 V. © 2010 American Chemical Society.

Screening interactions of zinc phthalocyanine-PPV oligomers with single wall carbon nanotubes - A comparative study - Bartelmeß, Jürgen; Ehli, Christian; Cid, Juan-Jose; Garcia-Iglesias, Miguel; Vazquez, Purificacion; Torres, Tomas; Guldi, Dirk Michael (Journal of Materials Chemistry, 2011)
In this paper, the ability to disperse single wall carbon nanotubes (SWNT) of several different-nature poly(p-phenylene vinylene) (PPV) oligomers having pendant zinc phthalocyanines (ZnPc) has been investigated. Based on the quenching of the ZnPc and SWNT fluorescence in the supramolecular assemblies, it has been shown that parameters such as p/n-type character of the oligomer, size and the distance between the ZnPc moiety and the conjugated backbone play an important role in the strength of the interactions. Important results suggest that n-type oligomers as well as certain flexibility in the phthalocyanine arrangement are breakthroughs for immobilizing SWNT in THF, affording stable and homogeneous suspensions. Transient absorption measurements confirm that upon photoexcitation the photoexcited ZnPc triggers an intraensemble charge transfer to yield oxidized ZnPc and reduced SWNT. © 2011 The Royal Society of Chemistry.

Synthesis and characterization of boron azadipyrromethene single-wall carbon nanotube electron donor-acceptor conjugates - Flavin, Kevin; Lawrence, Katherine; Bartelmeß, Jürgen; Tasior, Mariusz; Navio, Cristina; Bittencourt, Carla; O'Shea, Donal F.; Guldi, Dirk Michael; Giordani, Silvia (Acs Nano, 2011)
The preparation of a novel donor-acceptor material, consisting of a red/near-infrared (NIR) absorbing boron azadipyrromethene donor covalently attached to a highly functionalized single-wall carbon nanotube (SWNT) acceptor, which bears great potential in the field of organic photovoltaics, has been demonstrated. Both purification and covalent functionalization of SWNTs have been demonstrated using a number of complementary characterization techniques, including atomic force microscopy, Raman, X-ray photoelectron spectroscopy (XPS), Fourier transform infrared, and NIR-photoluminescence spectroscopy, and a functionalization density of approximately 1 donor molecule per 100 SWNT atoms has been estimated by XPS. The redox behavior of the fluorophore has been investigated by electrochemistry and spectroelectrochemistry as well as by pulse radiolysis. The donor-acceptor properties of the material have been characterized by means of various spectroscopic techniques, such as UV-vis NIR absorption spectroscopy, steady-state and time-resolved fluorescence spectroscopy, and time-resolved transient absorption spectroscopy. Charge transfer from the photoexcited donor to the SWNT acceptor has been confirmed with a radical ion pair state lifetime of about 1.2 ns. © 2011 American Chemical Society.

Tuning and optimizing the intrinsic interactions between phthalocyaninebased PPV oligomers and single-wall carbon nanotubes toward n-type/p-type - Bartelmeß, Jürgen; Ehli, Christian; Cid, Juan-Jose; Garcia-Iglesias, Miguel; Vazquez, Purificacion; Torres, Tomas; Guldi, Dirk Michael (Chemical Science, 2011)
In this work we have developed a strategy to immobilize functional groups such as ZnPc onto the surface of SWNT without, however, the needs of covalent functionalization, using substituted PPVoligomers (1-4) with different electronic character. The complementary use of a series of microscopies and spectroscopies is central, especially to gather a comprehensive picture of the mutual interactions. Importantly, only 1, bearing electron-withdrawing CN substituents, interacts tightly with SWNT affording stable and finely dispersed SWNT suspensions. 2-4, on the other hand, fail to disperse SWNT in THF following our newly developed protocol. A likely rationale is the p-type character of PPVoligomers 2-4, which imposes repelling forces relative to p-type SWNT, while placing CN groups yields n-type PPV-oligomer 1 and, in turn, strengthens the π-π interactions with SWNT. Photoexcitation of SWNT/1 hybrids generates a metastable radical ion pair state, namely oxidized ZnPc and reduced SWNT. Quite remarkable is the ratio of charge separation to charge recombination, namely nearly 3 orders of magnitude, which is encouraging to fabricate photovoltaic cells that are based, for example, on different nanocarbons. © The Royal Society of Chemistry 2011.